Cross-country econometric study on the impact of fiscal incentives on FDI - Ma. Laarni D. Revilla (Philippine Institute for Development Studies (PIDS), 2016)
The increasing level of competition for foreign direct investment (FDI) in the 1990s triggered many countries to offer various fiscal incentives. Specifically, many Asian countries persistently keep their tax rates competitive. To empirically investigate the relationship between the two variables, this paper examines the impact of fiscal incentives on FDI using panel data from 1996 to 2012 for five ASEAN countries. The analysis utilized five-panel data regression models, of which two are fixed-effects models and the remaining three are random-effects models. The results show that tax rate is negatively related to FDI. Another finding reveals the importance of infrastructure in increasing FDI. However, there is no significant link between governance indicators and FDI. To prevent a "race-to-the-bottom" effect on tax rates, the study recommends closer coordination between ASEAN countries in determining the optimal size and scope of these tax rates and other investment incentives. Additionally, focus on other country-specific factors affecting FDI flows, such as infrastructure, income, and population, is encouraged.
Keywords: 330; ASEAN; fiscal incentives; foreign direct investments; tax policy; tax competition